The nine : [large type] the true story of a band of women who survived the worst of Nazi Germany - Strauss, Gwen (Thorndike Press large print nonfiction, 2021)
"The Nine follows the true story of the author's great aunt Hélène Podliasky, who led a band of nine female resistance fighters as they escaped a German forced labor camp and made a ten-day journey across the front lines of WWII from Germany back to Paris. The nine women were all under thirty when they joined the resistance. They smuggled arms through Europe, harbored parachuting agents, coordinated communications between regional sectors, trekked escape routes to Spain and hid Jewish children in scattered apartments. They were arrested by French police, interrogated and tortured by the Gestapo. They were subjected to a series of French prisons and deported to Germany. The group formed along the way, meeting at different points, in prison, intransit, and at Ravensbrück. By the time they were enslaved at the labor camp in Leipzig, they were a close-knit group of friends. During the final days of the war, forced onto a death march, the nine chose their moment and made a daring escape. Drawing on incredible research, this powerful, heart-stopping narrative from Gwen Strauss is a moving tribute to the power of humanity and friendship in the darkest of times"--